“In the beginning was the Word”: words and deeds of Soviet economists in the book “Cognitive structures and political economy of socialism in the USSR”, ed. by P. A. Orekhovskii - D. V. Melnik (Russian Journal of Economics and Law)
Objective: to evaluate the work “Cognitive structures and political economy of socialism in the USSR”, ed. by P.A. Orekhovsky (St. Petersburg: Aleteya, 2022).Methods: textual analysis, methodological criticism.Results: the paper reviews a collective monograph by the Institute of Economics of the Russian Academy of Sciences devoted to the history of Soviet economic thought in the 1950s – first half of the 1980s. The novelty of the reviewed work consists in the methodological approach. It involves analyzing the peculiarities of speech practices and assumes that their result was the formation of a special cognitive structure, which development cycle had a decisive influence on political processes. Not being a tutorial, the work can be used as auxiliary educational material on the history of Soviet economy and economic thought. At the same time, the work contains a number of controversial points. In general, it presents an important contribution to a potential discussion of the past and present of the Russian economic science and the nature of late-Soviet and post-Soviet economic and social changes.Scientific novelty: the innovation of the work consists in the consistent application of the approach to the history of Soviet economic science, which implies blurring of a clear boundary between the subject and object of economic research. The originality of the methodological approach consists in the fact that it applies Western “postmodernism” to analyze such a unique object as the Soviet economic science.Practical significance: the work can be recommended to a wide range of specialists interested in the problems under consideration.